2018
DOI: 10.1002/adfm.201706785
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Modulated Band Alignment in CdS Nanorod/SnSx Nanosheet Hierarchical Heterojunctions toward Efficient Water Splitting

Abstract: CdS is a promising visible light response photoanode of photoelectrochemical (PEC) water splitting, but it remains a great challenge for practical application, due to the photohole‐induced self‐corrosion, and sulfide/sulfite ions as hole scavengers are always necessary for stable solar hydrogen generation. Herein, a CdS/SnSx nanorods/nanosheets hierarchical heterostructure with novel phase‐engineered band alignment is rationally designed via a two‐step solution reaction route for PEC water splitting. In the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 50 publications
1
53
0
1
Order By: Relevance
“…[42,43] [42,44] and summarized in Table S3 in the Supporting Information. [42,43] [42,44] and summarized in Table S3 in the Supporting Information.…”
Section: Photodetectorsmentioning
confidence: 99%
“…[42,43] [42,44] and summarized in Table S3 in the Supporting Information. [42,43] [42,44] and summarized in Table S3 in the Supporting Information.…”
Section: Photodetectorsmentioning
confidence: 99%
“…The V on shifts negatively to 0.16 Vf rom 0.39 V. Thephotoconversion efficiencies (h ABPE )under different bias voltages are calculated in the Supporting Information, Figure S11, indicating that SnS 2 -P has an obvious improvement over the measured potential range.F igure 3b shows the UV/Vis absorption curves and corresponding Tauc plots.S nS 2 -P exhibits higher light harvesting capability with stronger absorption and narrower E g (1.87 eV). [29] TheA rp lasma treated SnS 2 provides more surface-active sites and more reaction area than SnS 2 . Cyclic voltammograms in the non-Faradaic region (0.8-0.9 Vvs.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[3][4][5] As a narrow bandgap n-type semiconductor (2.4 eV), CdS has been widely studied as a typical PEC photoanode, owing to its visible-light absorption, high charge mobility, appropriate band position for water redox reaction. [18][19][20][21][22] The sulfide/sulfite ions as hole scavengers are always necessary for stable operation. [10][11][12][13][14][15][16][17] However, many studies have revealed that the PEC activity of pure CdS is severely limited because of the highly photogenerated carrier recombination.…”
Section: Introductionmentioning
confidence: 99%